APLIKASI CELUP IKAT DAN BATIK MOTIF BAMBU INSPIRASI MONUMEN PERJUANGAN MARKAS TKR DIVISI III PADA READY TO WEAR DELUXE - Gunawan, Alya Salsabila; Suharno, Suharno; Djuniwarti, Djuniwarti (Institut Seni Indonesia Padangpanjang, 2024)
The creation of this work is based on the empirical fact that, the Struggle Monument of TKR Division III Headquarters has never been used as a batik motif made with batik writing and stamp techniques. Therefore, the purpose of this work is to add batik motifs whose motifs contain historical values of the struggle of the Indonesian nation. Ready to wear deluxe was chosen as an application medium combined with tie dye techniques because the segmentation of this work is the upper middle class who like this type of clothing. To achieve this goal, the creation method used is exploration, design and embodiment with visual reference to the 2024/2025 Resilient fashion trend, namely Heritage sub-theme Reminiscence. The result of the creative process of this work is four deluxe ready to wear looks with casual ethnic styles presented at Indonesia International Modest Fashion 2023.